Singapore : Selected Issues. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2000)
Singapore's economic growth has been heavily dependent on factor accumulation during the past three decades. Attempts to gauge productivity growth in Singapore and other East Asian countries has led to the widely publicized debate on whether the East Asian 'miracle' was driven by factor accumulation or productivity growth. According to the most recent study by the authorities, Singapore's productivity growth was indeed very low until the 1980s, but has improved significantly to a level comparable to the Organization for Economic Co-operation and Development (OECD) average in the 1990s.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet